Proper cytoskeleton α‐tubulin distribution is concomitant to tyrosine phosphorylation during in vitro capacitation and acrosomal reaction in human spermatozoa. Issue 9 (16th September 2020) - Sáez‐Espinosa, Paula; Ferrández‐Rives, Mariola; Huerta‐Retamal, Natalia; Robles‐Gómez, Laura; Aizpurua, Jon; Romero, Alejandro; Gómez‐Torres, María José
Abstract: Spermatozoa motility is a key parameter during the fertilization process. In this context, spermatozoa tyrosine protein phosphorylation and an appropriate cytoskeleton α‐tubulin distribution are some of the most important physiological events involved in motility. However, the relationship between these two biomarkers remains poorly defined. Here, we characterized simultaneously by immunocytochemistry the α‐tubulin (TUBA4A) distribution and the tyrosine phosphorylation at flagellum before capacitation, during different capacitation times (1 and 4 hr), and after acrosome reaction induction in human spermatozoa. We found that the absence of spermatozoa phosphorylation in tyrosine residues positively and significantly correlated ( p  < 0.05) with the terminal piece α‐tubulin flagellar distribution in all physiological conditions. Conversely, we observed a positive significant correlation ( p  < 0.01) between phosphorylated spermatozoa and continuous α‐tubulin distribution in spermatozoa flagellum, independently of the physiological condition. Similarly, the subpopulation of spermatozoa with tyrosine phosphorylated and continuous α‐tubulin increases with longer capacitation times and after the acrosome reaction induction. Overall, these findings provide novel insights into the post‐transcriptional physiological events associated to α‐tubulin and the tyrosine phosphorylation during fertilization, which present potential implications for the improvement of spermatozoa selection methods.